2015
DOI: 10.1521/aeap.2015.27.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, HIV-Related Stigma, and Condom Use Among a Predominantly Rural Sample of HIV-Positive Men Who Have Sex With Men (MSM)

Abstract: Most previous studies of the sexual behaviors of men who have sex with men (MSM) living with HIV are based on samples recruited within relatively urban and suburban areas of the United States. Using an internet-based questionnaire, we assessed HIV-related stigma, loneliness, and event-level sexual behaviors in a sample of HIV positive MSM (n = 100) residing within a largely rural area in the Midwestern United States. HIV-related stigma was correlated with loneliness (r = 0.619, p < 0.01). Loneliness was negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 63 publications
5
39
1
Order By: Relevance
“…The original intervention brought together healthcare professionals (nurses) and patients (PLWH) from the same health facility for a 2-day workshop, facilitated by a representative from each target group, followed by a 1-day project evaluation workshop after a 1-month interval. The intervention included three key elements: (1) Sharing of information, (2) increasing contact between HW and PLWH, and (3) utilizing empowerment strategies to improve coping with HIV-related stigma. A full description of the original intervention is provided elsewhere.…”
Section: Original Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original intervention brought together healthcare professionals (nurses) and patients (PLWH) from the same health facility for a 2-day workshop, facilitated by a representative from each target group, followed by a 1-day project evaluation workshop after a 1-month interval. The intervention included three key elements: (1) Sharing of information, (2) increasing contact between HW and PLWH, and (3) utilizing empowerment strategies to improve coping with HIV-related stigma. A full description of the original intervention is provided elsewhere.…”
Section: Original Interventionmentioning
confidence: 99%
“…H IV-related stigma presents a significant barrier for both the prevention and management of HIV. [1][2][3] Despite advances in the medical treatment of HIV, the persistence of HIV-related stigma within healthcare settings in the United States (US) 4 continues to be an obstacle to improving the health and well-being of people living with HIV (PLWH). [5][6][7] Whether experienced or anticipated, HIV-related stigma may adversely affect the health behaviors, and, hence, the treatment outcomes of PLWH in a number of ways.…”
Section: Introductionmentioning
confidence: 99%
“…An association between homophobic stigma and risk-taking behaviors has been found [43]. Another study showed that as loneliness increased, condom use among MSM decreased [44]. Therefore, we chose self-esteem and loneliness as psychosocial factors in addition to anxiety, depression, and sexual compulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of research has documented the physical and mental health consequences of HIV-related stigma, both in China and globally (Hua et al, 2014; Kalichman, 2014; Karamouzian, Akbari, Haghdoost, Setayesh, & Zolala, 2015; Peitzmeier, Grosso, Bowes, Ceesay, & Baral, 2015). Negative consequences include non-adherence to antiretroviral therapy (ART) (Dlamini et al, 2009), irregular patterns of accessing health care (Evangeli, Newell, Richter, & McGrath, 2014), increased HIV symptoms (Earnshaw, Lang, Lippitt, Jin, & Chaudoir, 2015), loneliness (Hubach et al, 2015), and decreased quality of life (Slater et al, 2015; Wu et al, 2014). Stigma can be divided into perceived stigma , defined as negative beliefs, views, and feelings toward oneself arising from self-identification with a stigmatized condition (Logie & Gadalla, 2009), and enacted stigma , which refers to the experiences of prejudice, discrimination, and exclusion directed towards individuals from an external source because of specific attributes or conditions that characterize them (Brown, Macintyre, & Trujillo, 2003).…”
Section: Introductionmentioning
confidence: 99%